PENERAPAN IOT UNTUK MONITORING PEMBERIAN PAKAN IKAN OTOMATIS PADA AKUARIUM DI PERIKANAN SV IPB - Aep Setiawan; Erlin Arlitasari; Mahfuddin Zuhri; Andri Hendriana (Jurnal Informatika Teknologi dan Sains, 2022)
Fish feeding is one of the things that needs to be considered in aquaculture so that the fish produced are of high quality. Activities in fisheries at the Sokasi IPB school, the majority of which are still carried out manually, are fish feeding activities. Based on these problems, a system was designed that can control and monitor the process of feeding and supplying fish feed automatically using nodeMCU ESP8266. The tool can be accessed anywhere and anytime through the Blynk app. It is hoped that this tool can be used as a solution so that fish feeding activities in the Fisheries of the IPB Vocational School become faster, easier, and more efficient. Fish are fed according to the scheduled time with an appropriate dose. The process of feeding fish and feed supplies can be monitored remotely through the Blynk application. Alerts in the form of notifications and alarm sounds coming from the buzzer will be active if the value of the feed supply is smaller than 5 cm. The error value processed from the test is 0%.